Penerapan Model Pembelajaran Tipe Jigsaw Berbasis Media Gambar Pahlawan Untuk Meningkatkan Karakter Dan Hasil Belajar IPS (Sejarah) Siswa Kelas VIII-C SMP Negeri 2 Denpasar - Anto, Ruli; Sartika, Lianda Dewi; Sumasari, Ni Luh Putu (Medan Resource Center, 2024)
This study aims to examine the effectiveness of implementing the Jigsaw cooperative learning model using hero image media to improve the character and learning outcomes in Social Studies (History) among Grade VIII-C students of SMP Negeri 2 Denpasar in the 2023/2024 academic year. The research focuses on enhancing students' character and academic achievement. The study employs a Classroom Action Research (CAR) method based on Arikunto's model, which includes planning, action, observation, and reflection. The subjects of this study were 15 Grade VIII-C students. The results revealed improvements from Cycle I to Cycle II, with the number of students categorized as having